Pengaruh Kualitas Produk dan Kualitas Pelayanan terhadap Keputusan Pembelian Produk Unit Body Kepala Truck di PT Dragon Kencana Motor Gunung Sindur Bogor - Hati, Jasica Asih; Pasaribu, Veta Lidya Delimah (Jurnal Disrupsi Bisnis, 2024)
This study aims to determine the influence of product quality and on the purchase decision of truck head body unit products at PT Dragon Kencana Motor in Gunung Sindur, Bogor. It is a type of quantitative descriptive research using linear regression. The results showed that product quality variables had a positive and significant effect on purchasing decisions with a significance value of 0.000 < 0.05, and a calculated value of 7,045 > table of 1,984. Service quality variables have a positive and significant effect on purchasing decisions with a sig of 0.041 < 0.05, and a calculated value of 2,070 > table of 1,984. Simultaneously, the variables of product quality and service quality have a positive and significant effect on purchasing decisions with a Fcalculate value of 41,459 > 2.70 with a significance of 0.000 < 0.05.